Deteksi Osilasi Masalah Penalaan Pengendali secara Real-time dengan Metode Deteksi Puncak Spektrum - Permana, Boby Aoliya; Wardana, Awang Noor Indra (Faculty of Engineering, Universitas Tanjungpura, 2019)
In process industry, most control loops suffer with disturbances indicated by existing oscillations. One of the major problems of the oscillation is controller tuning problem. Peak spectral detection method which is classic and simple way is proposed as technique for detecting oscillation. Nevertheless, the utilization and performance of peak spectral detection on process oscillation detection still cannot be found. This study develops the utilization and performance of peak spectral detection method. It implemented based on IEC 61499. To evaluate the method, test data are used to set the lag value in peak spectral detection method and industrial data for obtaining performance of peak spectral detection method. With fast Fourier transform length 512 points and lag value 180 points, the developed peak spectral detection method detected two oscillations of three different oscillating signals at 461 s and 441 s.